Interpretation of Al-Nazafah concept among islamic scholars and its role in curbing the dangerous epidemic covid-19 / Zainab Hisham …[et al.]. - Hisham, Zainab; Mustafa@Busu, Zanirah; Junoh, Noraini; Nik Wan, Nik Zam; Nik Din, Nik Muniyati; Muhammad Hashim, Nurhidayah; Yusoff, Zulkarnain (Human Resource Management Academic Research Society, 2022)
Personal hygiene is very important because it is closely related to the level of faith of a Muslim individual. Every Muslim individual must maintain personal hygiene, as required by Islamic law, to prevent the risk of disease transmission to self, family, and society. Most diseases are transmitted by direct contact with the patient or indirectly by touching an object held by the patient. In the last 14 centuries, Rasulullah SAW has already emphasized hygiene, but the spread of various diseases is because of human negligence itself. Around the world, impressed by this dangerous epidemic. Therefore, various high authority parties came down to work together in guiding the community to stop the spread of this epidemic. This study explains the concept of Al-Nazafah according to Islamic doctrine and its role in curbing disease outbreaks, especially COVID-19. In addition, this study aims to present an interpretation of Al-Nazafah terminology and guidelines on personal hygiene according to the views of scholars so that it can be made a daily practice by the Muslim community, especially in the prevention of COVID-19 infection. This research uses the qualitative descriptive research method. It is done according to the method of library research, which is referenced through journals, books, the internet, and so on through the study of previous studies and the views of religious doctrines that are authoritative. The findings of this study are about the importance of the Muslim community’s concern and understanding of hygiene practices as recommended by religious doctrine and the Ministry of Health Malaysia (MOH). It is hoped that the results can be used as a guide by the entire Muslim community, especially in Malaysia, at various ages. The care of this practice must be taken seriously in further strengthening the practice of personal hygiene as the duty of every Muslim individual, especially in the containment of COVID-19 disease.